Transient osteoporosis of the hip in pregnancy: a report of three cases - (:unkn) unknown (My University, 2004)
Transient osteoporosis of the hip is a rare disease of unknown etiology. It is usually seen in middle-aged men and women in the third trimester of pregnancy and is associated with hip pain. It typically runs a benign course with eventual resolution of symptoms. We report three patients who presented with unilateral hip pain that started in the third trimester of pregnancy. Diagnosis of transient osteoporosis of the hip was made with the help of clinical and radiologic studies. Treatment was comprised of pain control therapy with diclofenac sodium (100 mg/day) for three months, bed rest for a month followed by mobilization with a walking aid. The follow-up period was at least 24 months. Clinical improvement occurred in the third month in one patient, and at the end of six months in the remaining patients. Complete radiologic improvement was seen at the end of 12 months.
Keywords: Adult; Female; Humans; Pregnancy; Pregnancy Complications; Diagnosis, Differential; Pain; Anti-Inflammatory Agents, Non-Steroidal; Prenatal Diagnosis; Bed Rest; Osteoporosis; Pregnancy Trimester, Third; Diclofenac; Hip Joint